Meta Analisis Media Pembelajaran Biologi Berbasis Potensi Lokal Terhadap Hasil Belajar Siswa - Etika, Anjar Dwi; Setiadi, Anandita Eka; Qurbaniah, Mahwar (Universitas Indraprasta PGRI Jakarta, 2024)
Learning media based on local potential is very important in improving student learning outcomes. This study aims to analyze the use of local potential-based biology learning media and its effect on learning outcomes. The research method used meta-analysis by reviewing articles related to local potential-based biology learning media published in national and international journals. Data were analyzed qualitatively narrative. The data sample analyzed 21 articles that present data on the effect of local potential-based biology learning media on learning outcomes. The results showed that the local potential of the region (plantae, Animalia, gene diversity, species, and mangroves), plants (tuberous food plants, mosses, reeds, traditional medicinal plants, and coffee plants), fungi, animals (gold snails, fish, coral reef waste) and exisitems (hills and green valleys,). Learning media that utilize local potential are visual and audio visual media. Visual media consists of pictures, posters, modules, booklets, textbooks, hand outs, props (analog), identification cards, and infographics. While audio visual is flash media macro. Local potential-based learning media affects learning outcomes with an effect size value of 1.15 (high). It is concluded that the learning media biology learning media based on local potential has a high effect on student learning outcomes.